La mutinerie d’Attica en septembre 1971. Récit d’une action collective - Philippe Artières (Criminocorpus)
The uprising of more than 1,000 inmates at Attica Penitentiary in New York State in September 1971 is an important event in the history of the visibility of prisoner resistance to the prison system. For three days, the mutineers occupied one of the establishment's courses under the watchful eye of journalists and cameras, drafting demands and talking to a committee of observers. The story of this mutiny allows us to grasp in detail the collective organization of this event which was repressed in a bloodbath.